Board demography and divestitures: The impact of gender and racial diversity on divestiture rate and divestiture returns. Issue 2 (April 2020) - Kolev, Kalin D.; McNamara, Gerry
Abstract: Drawing on resource dependence theory and group diversity research, this paper examines how board gender and racial diversity impact corporate divestitures. We argue that due to the diverse experiences, knowledge, and perspectives that female and racial minority directors bring to the boardroom, it is more difficult and time-consuming for the board to reach a consensus and pursue a common course of action. Consistent with this argument, our results indicate that board gender and racial diversity lead to longer divestiture completion times and a lower divestiture rate. Additionally, we argue that due to their cognitive heterogeneity, diverse boards likely exchange a greater variety of information, engage in more thorough discussions, and implement greater oversight of divestitures, leading to more positive divestitures returns. Offering mixed support for this argument, we found that while gender diversity increased divestiture returns, racial diversity was associated with lower divestiture returns.